Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(\sqrt{75\cdot48}=\sqrt{25\cdot3\cdot48}=\sqrt{25\cdot144}=\sqrt{25}\cdot\sqrt{144}=5\cdot12=60\)
b) \(\sqrt{2,5\cdot14,4}=\sqrt{25\cdot144\cdot\frac{1}{100}}=\sqrt{25}\cdot\sqrt{144}\cdot\sqrt{\frac{1}{100}}=5\cdot12\cdot\frac{1}{10}=6\)
a)\(\sqrt{45.80}=\sqrt{9.400}=\sqrt{9}.\sqrt{400}=3.20=60\)
b) \(\sqrt{75.48}=\sqrt{25.3.16.3}=\sqrt{5^2.3^2.4^2}=5.4.3=60\)
c)\(\sqrt{90.6,4}=\sqrt{10.9.4.1,6}=\sqrt{4^2.3^2.2^2}=4.3.2=24\)
d) \(\sqrt{2,5.14,4}=\sqrt{\dfrac{25}{10}.\dfrac{144}{10}}=\sqrt{\dfrac{25.144}{100}}=\sqrt{\left(\dfrac{5.12}{10}\right)^2}=\dfrac{5.12}{10}=6\)
a) \(\sqrt{45.80}=\sqrt{9.400}=\sqrt{9}.\sqrt{400}=3.20=60\)
b)\(\sqrt{75.48}=\sqrt{25.3.3.16}=5.3.4=60\)
c)\(\sqrt{90.6,4}=\sqrt{9.64}=3.8=24\)
d)\(\sqrt{2,5.14,4}=\sqrt{\dfrac{25}{10}.\dfrac{144}{10}}=\sqrt{\dfrac{25.144}{100}=\dfrac{5.12}{10}=\dfrac{60}{10}=6}\)
\(1)\) Ta có :
\(\left(\sqrt{3\sqrt{2}}\right)^4=\left[\left(\sqrt{3\sqrt{2}}\right)^2\right]^2=\left(3\sqrt{2}\right)^2=9.2=18\)
\(\left(\sqrt{2\sqrt{3}}\right)^4=\left[\left(\sqrt{2\sqrt{3}}\right)^2\right]^2=\left(2\sqrt{3}\right)^2=4.3=12\)
Vì \(18>12\) nên \(\left(\sqrt{3\sqrt{2}}\right)^4>\left(\sqrt{2\sqrt{3}}\right)^4\)
\(\Rightarrow\)\(\sqrt{3\sqrt{2}}>\sqrt{2\sqrt{3}}\)
Vậy \(\sqrt{3\sqrt{2}}>\sqrt{2\sqrt{3}}\)
Chúc bạn học tốt ~
a: \(=2\cdot3+\sqrt{15}-2\sqrt{15}=6-\sqrt{15}\)
b: \(=5\sqrt{10}+2\cdot5-5\sqrt{10}=10\)
c: \(=2\sqrt{7}\cdot\sqrt{7}-\sqrt{12}\cdot\sqrt{7}-\sqrt{7}\cdot\sqrt{7}+2\sqrt{21}=2\cdot7-7=7\)
d: \(=\left(2\sqrt{11}-3\sqrt{2}\right)\cdot\sqrt{11}+3\sqrt{22}=2\cdot11=22\)
a) Ta có: \(\sqrt{0.1}\cdot\sqrt{4000}\)
\(=\sqrt{\frac{1}{10}}\cdot\sqrt{4000}\)
\(=\sqrt{\frac{1}{10}\cdot4000}=\sqrt{400}=20\)
b) Ta có: \(\sqrt{\frac{9}{196}}=\sqrt{\left(\frac{3}{14}\right)^2}\)
\(=\left|\frac{3}{14}\right|\)
\(=\frac{3}{14}\)(Vì \(\frac{3}{14}>0\))
c) Ta có: \(\sqrt{16}\cdot\sqrt{36}-\sqrt{125}:\sqrt{0.01}\)
\(=\sqrt{16\cdot36}-\frac{\sqrt{125}}{\sqrt{\frac{1}{100}}}\)
\(=\sqrt{576}-\sqrt{125:\frac{1}{100}}\)
\(=24-\sqrt{125\cdot100}\)
\(=24-\sqrt{12500}\)
\(=24-50\sqrt{5}\)
d) Ta có: \(\left(\sqrt{112}-\sqrt{63}+\sqrt{7}\right):\sqrt{7}\)
\(=\left(4\sqrt{7}-3\sqrt{3}+\sqrt{7}\right):\sqrt{7}\)
\(=\frac{2\sqrt{7}}{\sqrt{7}}=2\)
e) Ta có: \(\sqrt{2.5}\cdot\sqrt{30}\cdot\sqrt{48}\)
\(=\sqrt{\frac{5}{2}\cdot30\cdot48}=\sqrt{3600}=60\)
a)
\(4\sqrt{7}=\sqrt{4^2.7}=\sqrt{112}\)
\(3\sqrt{13}=\sqrt{3^2.13}=\sqrt{117}\)
\(\sqrt{112}< \sqrt{117}\Rightarrow 4\sqrt{7}< 3\sqrt{13}\)
b) \(3\sqrt{12}=\sqrt{3^2.12}=\sqrt{9.2^2.3}=2\sqrt{27}>2\sqrt{16}\)
c)
\(\frac{1}{4}\sqrt{82}=\sqrt{\frac{82}{16}}=\sqrt{\frac{41}{8}}=\sqrt{5+\frac{1}{8}}\)
\(6\sqrt{\frac{1}{7}}=\sqrt{\frac{36}{7}}=\sqrt{5+\frac{1}{7}}\)
\(\sqrt{5+\frac{1}{8}}< \sqrt{5+\frac{1}{7}}\Rightarrow \frac{1}{4}\sqrt{82}< 6\sqrt{\frac{1}{7}}\)
d)
\(\frac{1}{2}\sqrt{\frac{17}{2}}=\sqrt{\frac{17}{8}}=\sqrt{2+\frac{1}{8}}\)
\(\frac{1}{3}\sqrt{19}=\sqrt{\frac{19}{9}}=\sqrt{2+\frac{1}{9}}\)
\(\sqrt{2+\frac{1}{8}}>\sqrt{2+\frac{1}{9}}\Rightarrow \frac{1}{2}\sqrt{\frac{17}{2}}> \frac{1}{3}\sqrt{19}\)
e)
\(3\sqrt{3}-2\sqrt{2}=\sqrt{27}-\sqrt{8}\)
Mà \(\sqrt{27}>\sqrt{25}; \sqrt{8}< \sqrt{9}\Rightarrow \sqrt{27}-\sqrt{8}> \sqrt{25}-\sqrt{9}=5-3=2\)
Vậy \(3\sqrt{3}-2\sqrt{2}>2\)
f)
\(\sqrt{7}+\sqrt{5}< \sqrt{9}+\sqrt{9}=6\)
\(\sqrt{49}=7\)
\(\Rightarrow \sqrt{7}+\sqrt{5}< 6< 7=\sqrt{49}\)
g)
\(\sqrt{2}< \sqrt{3}; \sqrt{11}< \sqrt{25}=5\)
\(\Rightarrow \sqrt{2}+\sqrt{11}< \sqrt{3}+5\)
h) Lặp lại câu d
i)
\(\sqrt{21}>\sqrt{20}\); \(\sqrt{5}< \sqrt{6}\)
\(\Rightarrow \sqrt{21}-\sqrt{5}> \sqrt{20}-\sqrt{6}\)
\(2.3+\sqrt{15}-2\sqrt{15}=6-\sqrt{15}\)
\(5\sqrt{10}+2.5-5\sqrt{10}=10\)
\(14-2\sqrt{21}-7+2\sqrt{21}=7\)
\(33-3\sqrt{22}-11+3\sqrt{22}=22\)
1,\(4\sqrt{5}+2\sqrt{5}-\sqrt{5}-15\sqrt{5}=-10\sqrt{5}\)
2,\(8\sqrt{5}-15\sqrt{5}+15\sqrt{5}-3\sqrt{5}=5\sqrt{5}\)
3,\(\left(28\sqrt{3}+9\sqrt{3}-4\sqrt{3}\right):\sqrt{3}=33\)
4,\(7\sqrt{7a}+3\sqrt{7a}-2\sqrt{7a}=8\sqrt{7a}\)
5,\(-6\sqrt{a}-\sqrt{6a}+\sqrt{6a}=-6\sqrt{a}\)
6,\(8\sqrt{3}-12\sqrt{3}+5\sqrt{3}+2\sqrt{3}=3\sqrt{3}\)
\(\sqrt{2,5.14,4}=\sqrt{36}=+-6\)